The Influence of Lifestyle, Destination and Ewom's Image on the Decision to Visit Instagram Followers Explore Indonesia : Pengaruh Lifestyle, Citra Destinasi dan Ewom Terhadap Keputusan Berkunjung Followers Akun Instagram Explore Indoneisa - Dian Bagus Mujisantoso; Lilik Indayani (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine Lifestyle, Destination Image and Ewom on Decisions Against the Decision to Visit Instagram Explore Indonesian Users.This research includes quantitative research with hypothesis testing. The samples used in this study were 80 visitors on the Explore Indonesia Instagram account. The analytical tool used in this research is multiple linear regression analysis, determinant coefficient (R2), multiple correlation coefficient (R), f test, t test, and classic assumption test using SPSS version 18 for windows. Primary data in this study were obtained from questionnaires whose measurement used a Likert scale that was tested for validity and reliability.The results of the analysis prove that knowing Lifestyle, Destination Image and Ewom on Decisions on Visiting Decisions. Lifestyle influences visiting decisions, destination image affects visiting decisions, Ewom also affects visiting decisions.